E-Commerce Adoption Among Iraqi Companies: Does Context Matters? - Abdulsatar Abduljabbar Sultan; Mohamad Ghozali Hassan; Sarina Muhamad Noor (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The adoption of e-commerce by organisation has shown a phenomenal progress. Yet, to this date, studies conducted on this phenomenon are still insufficient. What is so glaring is that most of the empirical studies have adopted Rogers’s innovation-decision process model to analyze the adoption process, using only a portion of the model. This paper will elaborate the Diffusion of Innovation Theory (DOI) and highlight the moderating effect of civil conflict on the relationship between technological, organizational, and adoption of electronic commerce. The study will be conducted in Iraq, hence, the results will contribute to the extremely limited numbers of empirical studies that investigate e-commerce adoption in Arab countries. Data for this study will be collected using survey among SMEs owners. Structural Equation Model using SmartPLS will be used to analyse data.